Effectiveness of ICT-integrated pedagogy on pre-service teachers’ teaching competence in mathematics - Samantray, Ashapurna; Behera, Rashmi Ranjan; Acharya, Amulya Kumar (Frontiers in Education, 2024)
The influence of teachers' teaching competence on students' academic performance is pivotal, prompting an examination of the efficacy of ICT-integrated pedagogy in enhancing the teaching competence of pre-service mathematics teachers. This quasi-experimental research employed a pre-test, and post-test control group design involving 30 pre-service teachers, with 15 participants assigned to both the experimental and control groups. Throughout a four-week duration, the experimental group received instruction utilizing 'ICT-integrated pedagogy,' while the control group was taught applying traditional 'Lecture-based pedagogy.' Employing a 'Mathematics Teaching Competence Scale,' both cohorts were assessed prior to and following the intervention, with data subjected to analysis using descriptive statistics and t-tests in SPSS version 20. The results revealed that pre-service teachers in the experimental group, exposed to 'ICT-integrated pedagogy,' demonstrated superior mathematics teaching competency compared to their counterparts in the control group. These findings advocate for the positive impact of ICT-integrated pedagogical approaches in nurturing the teaching proficiency of preservice teachers. Consequently, this study suggests the widespread implementation of this approach by Teacher Educators, envisioning its potential to engender competent and highquality teachers.